Numéro spécial : Kin constellations languages waters futures - Eshraghi, Leuli; Moulton, Kimberly (Artlink, 2020)
In this edition, we consider Ancestral materiality, intellectual traditions and expressions spanning the great oceans, skies and lands connecting the kin and Country of First Peoples from around the world. We see the artistic, economic and cultural paradigms as a reflection on life and death, on black holes and shining stars illuminated as constellations in the night skies from the times of our Ancestors and traced in the footprints made on the lands we travel.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Queering Decolonization – Two Spirit Resistance Across Borders From Turtle Island to Palestine (2019)
Avec Alex Wilson, Jeffrey McNeil, Teddy Syrette, May Ela and Ahmed Maswadeh.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Interpellations: Three Essays on Kent Monkman - Thériault, Michèle (Galerie Leonard & Bina Ellen art gallery, 2012)
Trois essais de Richard W. Hill, Jonathan D Katz et Todd B Porterfield.
Section: 118 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé